Air‐Stable Solid Aryl and Heteroaryl Organozinc Pivalates: Syntheses and Applications in Organic Synthesis. Issue 38 (12th August 2014) - Manolikakes, Sophia M.; Ellwart, Mario; Stathakis, Christos I.; Knochel, Paul
Abstract A wide range of air‐stable, solid, polyfunctional aryl and heteroarylzinc pivalates were efficiently prepared by either magnesium insertion or Hal/Mg exchange followed by transmetalation with Zn(OPiv)2 (OPiv=pivalate). By reducing the amount of LiCl the air stability could be significantly enhanced compared with previously prepared reagents. An alternative route is directed magnesiation using TMPMgCl⋅LiCl (TMP=2, 2, 6, 6‐tetramethylpiperidyl) followed by transmetalation with Zn(OPiv)2 or, for very sensitive substrates, direct zincation by using TMPZnOPiv. These zinc reagents not only show excellent stability towards air, but they also undergo a broad range of CC bond‐formation reactions, such as allylation and carbocupration reactions, as well as addition to aldehydes and 1, 4‐addition reactions. Acylation reactions can be performed by using an excess of TMSCl to overcome side reactions of the omnipresent pivalate anion.